Acceptence of Information and Communication Technology Among Members of Youth Organisations in Kuala Lumpur - Alias, Jalili (2006)

(untitled)
Youth’s acceptance of information communication technology (ICT) is undeniably important. Based on our youth’s contribution to national labour supply, it is evident that this group is a major driving force of national development. However, there is still few studies done on Malaysian youth, especially on their readiness to accept ICT. This study focuses on determining the acceptance of ICT among members of youth associations in Kuala Lumpur. The specific objectives for this study are (1) to identify the level of ICT acceptance, (2) to identify the purpose of ICT usage, (3) to identify the relations between demographic factors, media exposure, peer influence and organizational support with ICT acceptance and (4) to identify the difference between ICT acceptance level with those who have undergo ICT training and those who have not among members of youth associations in Kuala Lumpur. 252 respondents of seven youth associations from seven areas have been chosen to represent the youth associations in Kuala Lumpur. Data was collected through questionnaires using the drop and collect method. After collection, data was analysed based on frequency, percentage, Pearson Correlation Test, T-test and the one way Anova test. This study found that acceptance of ICT is at medium level. The main objective for using computers is for writing and typing. The main objective of internet use is to seek information. There is a significant positive relationship between acceptance of ICT and respondent’s age as well as income. However, there is no significant relationship between acceptance of ICT and experience in associations or gender. There is significant difference between races, education level, work category and marriage status in acceptance of ICT. There is significant positive relationships between acceptance of ICT and media exposure regarding ICT. There is significant difference between respondents who have undergo formal ICT training and those who have not in accepting ICT. Organizational support and peer influence factors were found to have no significant relationship with acceptance of ICT among members of youth associations in Kuala Lumpur